Gaya Kepemimpinan terhadap Kinerja Sumber Daya Manusia: Moderasi Budaya Organisasi - Setyo Budi Prakoso; Ibnu Khajar (JUEB : Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the role of leadership style on the performance of Civil State Apparatus (ASN) with organizational culture as a moderating variable at the Regional Secretariat of Kotawaringin Barat Regency. A quantitative approach was employed using a saturated sampling technique, in which the entire population of 174 ASN served as research respondents. Data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results indicate that leadership style has a positive and significant effect on ASN performance, and organizational culture is similarly proven to have a positive and significant influence on employee work outcomes. Moreover, organizational culture is proven to moderate the relationship between leadership style and ASN productivity — meaning that the stronger the organizational culture, the greater the impact of leadership style in driving optimal work results. The coefficient of determination (R²) of 0.660 indicates that the model explains 66.0% of the performance variation examined, while the remaining 34.0% is attributed to variables outside the model. Practically, these findings suggest that government institution leaders should not only develop effective leadership styles, but also actively build and strengthen a conducive organizational culture as a strategic foundation for sustainably improving ASN performance.